Unregistered Divorce Practices in Rural Indonesian Muslim Communities: Legal and Cultural Dimensions - Diningrum, Aulia; Efendi, Rahmad (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2026)
Background: Unregistered divorce is carried out without going through the official procedure at the Religious Court, making it unrecognized under state law despite being valid according to Islamic law. This situation creates various legal issues, particularly regarding the legitimacy of registering children with the Civil Registry and Population Administration Office after such a divorce. Purpose: This study aims to analyze the interplay between legal norms and cultural practices in unregistered divorce highlighting how these practices affect the legal identity of children and exploring their implications within both Islamic legal thought and anthropological perspectives. Methods: This study employs an empirical juridical approach using field research methods. Primary data were obtained through interviews with community leaders, religious figures, and residents who engaged in unregistered divorces. Meanwhile, secondary data were collected from legal literature, statutory regulations, and other scholarly references. The analysis was conducted qualitatively through the stages of data reduction, data presentation, and conclusion drawing. Findings: The study reveals that unregistered divorce is often legitimized by cultural consensus and religious approval at the local level, despite its non-compliance with formal legal procedures. Such practices contribute to the exclusion of children from official civil registration, limiting their access to legal rights. The findings indicate that religious authority and local customs operate as parallel legal systems, occasionally challenging the state’s regulatory framework. Theoretical and Practical Implications: The research enriches anthropological approaches to Islamic jurisprudence by illustrating how fiqh adapts and transforms in localized contexts. Practically, it suggests the need for culturally sensitive legal reforms and community-based legal literacy programs to bridge the gap between state law and community practices. Originality/Novelty: This study is among the first to integrate an anthropological reading of fiqh with empirical legal research on unregistered divorce in Indonesia, offering a nuanced understanding of how local Muslim communities reconcile religious norms with socio-legal realities.